2022
DOI: 10.3389/fphar.2022.838647
|View full text |Cite
|
Sign up to set email alerts
|

Radix Astragalus Polysaccharide Accelerates Angiogenesis by Activating AKT/eNOS to Promote Nerve Regeneration and Functional Recovery

Abstract: Peripheral nerve injury (PNI) results in loss of neural control and severe disabilities in patients. Promoting functional nerve recovery by accelerating angiogenesis is a promising neuroprotective treatment strategy. Here, we identified a bioactive Radix Astragalus polysaccharide (RAP) extracted from traditional Chinese medicine (TCM) as a potent enhancer of axonal regeneration and remyelination. Notably, RAP promoted functional recovery and delayed gastrocnemius muscle atrophy in a rat model of sciatic nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Moreover, SCs secrete several signaling molecules, such as pro-inflammatory factors, cytokines, growth factors, neurotrophic factors and extracellular matrix molecules, to recruit macrophages, support neuronal survival and accelerate axonal regeneration. Finally, remyelinate regenerated axons and repel infiltrated macrophages to complete the process of peripheral nerve repair [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SCs secrete several signaling molecules, such as pro-inflammatory factors, cytokines, growth factors, neurotrophic factors and extracellular matrix molecules, to recruit macrophages, support neuronal survival and accelerate axonal regeneration. Finally, remyelinate regenerated axons and repel infiltrated macrophages to complete the process of peripheral nerve repair [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Muangsanit et al suggested that engineered neural tissue which contain aligned networks of ECs tube-like structures could provide both enhanced vascularization and direct support for regenerating axons [ 2 ]. Our previous study showed that Radix Astragalus polysaccharide enhanced functional recovery by accelerating angiogenesis after peripheral nerve injury (PNI) [ 3 ]. Therefore, adequate vascularization is not only important for providing essential nutrients for nerve regeneration and clearing degenerative and necrotic substances from injury site, but also essential for guiding SCs migration and specific reconnection from axons to target organs.…”
Section: Introductionmentioning
confidence: 99%
“…[40] Astragalus polysaccharide can also accelerate angiogenesis and promote axonal and myelin regeneration by activating the AKT/eNOS signaling pathway, presenting a positive effect on neural regeneration. [41] The gut microbiota and epithelial-mesenchymal transitions were the outbreak keywords in the last 4 years, potentially indicating new hotspots in the field of Huangqirelated research (Fig. 5C).…”
Section: Discussionmentioning
confidence: 99%
“…[40] Astragalus polysaccharide can also accelerate angiogenesis and promote axonal and myelin regeneration by activating the AKT/eNOS signaling pathway, presenting a positive effect on neural regeneration. [41]…”
Section: Discussionmentioning
confidence: 99%
“…It showed that iPSCs after induction had taken on hair follicle stem cell-like characteristics.Astragalus polysaccharide, as the main active substance in astragalus, has an excellent performance in anti-inflammatory, vascular protection and pro-angiogenesis. Zhang et al60 found that astragalus polysaccharide significantly enhanced the migration and tube formation of vascular endothelial cells through in vitro cellular and in vivo experiments with intrathecal injection of astragalus polysaccharide in sciatic nerve injury. Key proteins in the VEGF pathway were found by F I G U R E 6 (A) Trauma-related genes detected after 14 days in the three groups with different intervention modes.…”
mentioning
confidence: 99%